Implementation Effectiveness Analysis E-Government At The Bandar Agung Lahat District Office - M.Rizki Prayoga (KH. A. Wahab Hasbullah University, 2023)
This research analyzes the practice of implementing e-government at the governance horizon, namely the sub-district level. This research uses quantitative description. Apart from that, it is carried out through various media, both print, electronic and mass media, as well as through various public relations channels. The findings of this research indicate that the effectiveness of e-government in the current era is not yet optimal, as evidenced by its effectiveness in terms of efficiency, mass participation, and device adaptation with applications, development and life. Ideal conveniences in this case will enable society to participate in public procurement processes and contribute to the creation of smart cities by utilizing innovative new technologies in communication approaches with the public. Several steps can be taken between now and then, including building infrastructure, ensuring compliance with regulations, and creating new ones.